The Effect of Contemporary Management Accounting on Competitive Advantage through Market Capability as a Mediator - Chayprapak, Somkiat; Wichitsathian, Sareeya (KKBS Journal of Business Administration and Accountancy, 2025)
The study examines the effects of contemporary management accounting on competitive advantage through market capability as a mediator. The data were collected by using questionnaires from 193 companies listed on the Stock Exchange of Thailand. The hypothesis was tested using a partial least squares structural equation model (PLS-SEM). The results revealed that contemporary management accounting has a direct positive effect on market capability. In addition, market capability plays a role as a full mediator of contemporary management accounting that affects competitive advantage. The results of the research show that contemporary management accounting is important to market capability, which affects the increase of competitive capability of the business.